Characteristics of Soil Chemical Properties Associated with Inceptisols in Various Land Use in Jasinga, Bogor - Erlina Rahmayuni; Syaiful Anwar; Budi Nugroho; Lilik Tri Indriyati (JOURNAL OF TROPICAL SOILS, 2023)
Inceptisols are soils with low to moderate fertility and have not experienced further development. This study aims to characterize the chemical properties of inclusions and base exchange fractionation of P of soil on Inceptisol soil map units of forest land, dry land, and paddy fields in Jasinga. Soil samples were taken at three horizons (Ao or Ap, AB/B1, and B/Bt) on forest soil profiles and dry land, while on paddy fields, they were taken at a depth of 0-20 cm, 20-40 cm, and 40-60 cm from the surface land. The chemical properties of the soil analyzed were soil pH, C-organic, soil bases, P-total, CEC, base saturation, and P fractionation. The results showed that the chemical properties of inclusions in the Inceptisol Jasinga soil map unit included high CEC and BS and low Mn-dd. The dominant soil inclusions are in paddy fields, followed by forests, and the lowest is in dry land. The chemical properties findings did not significantly differentiate the available inorganic P, Al-P, (Fe, Mn)-P, and (Ca, Mg)-P fractions. The inclusion of chemical characteristics did not result in a reversal of the correlation with the inorganic P fraction.